PENGARUH KEPEMILIKAN MANAJERIAL DAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN UTANG SEBAGAI VARIABEL INTERVENING - Warapsari, A. A. Ayu Uccahati; Suaryana, I G.N. Agung (E-Jurnal Akuntansi, 2016)
The purpose of this study is to understand the direct and indirect influence of managerial and institutional ownership to a firm’s value with debt policy as an intervening variable. This study is conducted in a manufacture companies listed in Indonesian stock exchange from 2013 to 2014. Purposive sampling is used as a method of selecting the sample with three criteria which generate 30 companies as a viable sample observed. The analytical method used path analysis (path analysis). The results show that (1), Managerial ownership does not affect the debt policy, (2) Institutional ownershiphas negative effect on the debt policy, (3) Managerial ownership does not affect the firm’s value, (4) Ownership institutional does not affect the firm’s value, (5) debt policy has no effect on the firm’s value, (6) Debt policy fail to mediate the influence between managerial and institutional ownership on firm’s value.
Keywords: ownership structure; debt policy; firm’s value